The Islamic Republic of Australia - Shah, Sami ([Pymble, N.S.W.] : ABC Books, 2017)
From hijabs to jihad and everything in between - Muslims down under today What is Halal? A country bordering Shariahland, or a method of preparing food? Do the Five Pillars of Islam comply with modern building codes? Or are they simply a philosophy for living? And if Muslims first arrived in Australia as early as 1800, can they go back to where they came from? In this funny and informative exploration of Islam in Australia, award-winning comedian and writer Sami Shah takes us behind the stereotypes and generalisations to find out who Australian Muslims are, how they live and what they think. Along the way we meet everyone from a woman who runs a 'speed date a Muslim night' to a conservative Islamic preacher, and to the founder of a group called Muslims for Progressive Values. The result is an entertaining and fascinating snapshot of Islam down under today. Praise for Sami Shah: 'Humour at its most vigorous and unsparing' - Kirkus Reviews 'Stylish . . . newsy, bitingly funny' - Sunday Telegraph 'Raw, funny and inspiring' - Wendy Harmer.
Imprint: ABC Books.
Keywords: Comedy; Islam -- Australia -- Humor; Muslims -- Australia -- Attitudes; Religion and politics; Religion - General; Religion & politics; Australia -- Race relations; Australian; Sociology